A Late Medieval Sword from the River Wisła near Gniew (Mewe) in Pomerelia - Grzegorz Żabiński (Fasciculi Archaeologiae Historicae, 2017)
This paper discusses a find of a Late Medieval sword from the River Wisła near Gniew (Mewe) in Pomerelia. The sword is lavishly ornamented, both on its pommel and the blade. The pommel is decorated with a Greek cross. On the tang there are swordmaker’s marks made with a chisel. The blade is ornamented with incised marks, filled with nonferrous alloy: an S in a double circle, two crosses fourchée, a cross crosslet in a single circle, an A, an R, and a partially preserved cross pattée in a double circle. On the other flat there is a cross pattée in a single circle, two crosses fourchée, a six-petal rosette, an h, an E, and an S in a double circle. The sword can be classified as E. Oakeshott’s Type XIIIa, J, 2 and dated to c. 1300-1350.